Proceedings of the 30th Annual ACM SIGACT-SIGOPS Symposium on Principles of Distributed Computing 2011
DOI: 10.1145/1993806.1993829
|View full text |Cite
|
Sign up to set email alerts
|

Locally checkable proofs

Abstract: This work studies decision problems from the perspective of nondeterministic distributed algorithms. For a yes-instance there must exist a proof that can be verified with a distributed algorithm: all nodes must accept a valid proof, and at least one node must reject an invalid proof. We focus on locally checkable proofs that can be verified with a constanttime distributed algorithm. For example, it is easy to prove that a graph is bipartite: the locally checkable proof gives a 2-colouring of the graph, which o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(96 citation statements)
references
References 20 publications
(42 reference statements)
0
95
1
Order By: Relevance
“…However, one of the nodes in the bad instance has to raise an alarm-if we attempt to do this based on local information only, we will occasionally make false alarms. Even though the task is inherently global, we can still use local algorithms if we resort to proof labeling schemes [6,12,13]. If we are given just an arbitrary spanning tree T , we cannot verify it locally.…”
Section: Alarm Ok Okmentioning
confidence: 99%
“…However, one of the nodes in the bad instance has to raise an alarm-if we attempt to do this based on local information only, we will occasionally make false alarms. Even though the task is inherently global, we can still use local algorithms if we resort to proof labeling schemes [6,12,13]. If we are given just an arbitrary spanning tree T , we cannot verify it locally.…”
Section: Alarm Ok Okmentioning
confidence: 99%
“…Paper [12] generated several following up contributions, including, e.g., studies on the impact of randomization [11], studies on the impact of node identifiers [10], studies on verification tasks where certificates include node IDs [17], etc. See also [16] for other forms of local checking, and for their impact on distributed graph-optimization problems.…”
Section: Related Workmentioning
confidence: 99%
“…Recent work in this area includes but is not limited to, deciding locally whether the nodes of a network are properly colored , checking the results obtained from the execution of a distributed program [13,15], designing time lower bounds on the hardness of distributed approximation [7], estimating the complexity of logics required for distributed run-time verification [14], and elaborating a distributed computing complexity theory [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…The results where later on extended in [15] to the set agreement task and in [14] proving nearly tight bounds on the number of opinions required to check any distributed language. In [12,16] the context of local distributed network computing [23] is considered. It was shown that not all network decision tasks can be solved locally by a non-deterministic algorithm.…”
Section: Introductionmentioning
confidence: 99%